APLIKASI PENGUBAH DAYA TEGANGAN DC KE AC BERBASIS TRANSFORMATOR NON CT DAN TRANSISTOR MOSFET - Pambudi, Prastyono Eko (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2004)
Distorting of energy of tension DC to AC used to support the social life of society. There by will arise an problems form of electric current from PLN desisted sudden and long time. The problems of course can be disregarded with the installation of power plant byself like generator AC or use the accumulator. Using of transistor energy of type MOSFET also used especially at final of switching showing optimal performance. This matter is showing with the temperature speed which relative lower and ideal performance temperature stability. The result of comparison of output power and efficiency of changer of energy of tension DC to AC with the transformator non-CT indicate that the appliance can only work 90% from maximal appliance ability. This problems because of accumulator use ably small current or standart.